Identification and characterization of an indigoidine-like gene for a blue pigment biosynthesis in Streptomyces aureofaciens CCM 3239 - Nováková, Renáta; Odnogová, Zuzana; Kutaš, Peter; Fecková, Ľubomíra; Kormanec, Ján (Folia microbiologica, 2010)
An incomplete oligoketide (PK; 'polyketide') gene cluster, aur1, responsible for the production of an angucycline-like antibiotic auricin was identified in Streptomyces aureofaciens CCM 3239. A region downstream of the aur1 was cloned and sequenced, revealing 28 new genes encoding putative protein products involved in deoxysugar biosynthesis and other putative PK-related biosynthetic functions. In addition, a gene, bpsA, encoding a protein similar to non-ribosomal peptide synthetases (NRPSs) was identified in this region. A deduced protein product of the gene showed the highest similarity to NRPSs IndC from Erwinia chrysanthemi and BpsA from Streptomyces lavendulae, both involved in the biosynthesis of a blue pigment indigoidine. S. aureofaciens CCM 3239 was found to produce an extracellular blue pigment with identical properties as indigoidine. A deletion mutant of bpsA in S. aureofaciens CCM 3239 failed to produce the blue pigment. In addition, the deletion of bpsA had a positive effect on auricin production. The results indicate the involvement of the bpsA gene in biosynthesis of the indigoidine blue pigment in S. aureofaciens CCM 3239.
Keywords: regulace genové exprese u bakterií; bakteriální proteiny; financování organizované; Bacterial Proteins; Gene Expression Regulation, Bacterial; Financing, Organized; Molecular Sequence Data; Streptomyces aureofaciens; molekulární sekvence - údaje; Pigments, Biological; Piperidones; piperidony; biologické pigmenty